Resensi Buku: Sopo Ora Sibuk (SOS) - Marjuki (Jurnal Studi Multidisiplin Qomaruna, 2023)
This review examines "Sopo Ora Sibuk" (SOS) by Much Khoiri, a guide that presents an innovative approach to leveraging the challenges of busyness as a catalyst for writing inspiration. Spanning 167 pages, Khoiri describes 17 pragmatic strategies for managing to write amidst a hectic schedule. These methods encompass setting clear intentions, employing tools for capturing ideas, and integrating writing with prayer, highlighting the pivotal roles of time management and self-discipline in the creative process. Furthermore, the text delves into the 'maqam' of writing, detailing the various stages of the writer's journey from novice to enlightenment. Khoiri's ability to articulate his insights in accessible language renders the book particularly engaging for a broad audience. While there is potential for further refinement, SOS stands as a compelling resource for those seeking to sustain their writing productivity in the face of daily distractions. It convincingly argues that busyness, when approached correctly, can serve not as an impediment but as a stimulus for growth and creativity in writing.